If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(+6)-(5Y+7)Y=-2
We move all terms to the left:
(+6)-(5Y+7)Y-(-2)=0
We add all the numbers together, and all the variables
-(5Y+7)Y+6-(-2)=0
We add all the numbers together, and all the variables
-(5Y+7)Y+8=0
We multiply parentheses
-5Y^2-7Y+8=0
a = -5; b = -7; c = +8;
Δ = b2-4ac
Δ = -72-4·(-5)·8
Δ = 209
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:Y_{1}=\frac{-b-\sqrt{\Delta}}{2a}Y_{2}=\frac{-b+\sqrt{\Delta}}{2a}Y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-7)-\sqrt{209}}{2*-5}=\frac{7-\sqrt{209}}{-10}Y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-7)+\sqrt{209}}{2*-5}=\frac{7+\sqrt{209}}{-10}
| -2n-14=n+4 | | 7x+18=4x+60 | | 7r+5=5+8r | | 7x-3=18x=3 | | 5x-5=-2x+7x | | 1+2n=-7+3n | | x^2+32500=76600 | | 2x-4=18x=11 | | 2j+13=4j-5 | | x^2+200x=166400 | | -6v+4(v+8)=38 | | 4(2)^(-4x)+2=66 | | 76-8z=2(z-2) | | 4(2)^-4x+2=66 | | p+(2+3)=10 | | -0.3x–4=9.4 | | –11=x+5 | | (7+2x)^2=11 | | 12=w12 | | t=-16t2+48t+4 | | 6v+15=2v+47 | | 3x+-1(x+-7)=18 | | x+10=-5x-4 | | 16^2+x^2=27^2 | | 22.5+2y=7y+11 | | F(4)=6x-10 | | 6p+3p-5=112 | | 5w+1=6w+5 | | ∠1=(6x+5)°,∠2=(11x+12) | | x²-27x=0 | | 4e=58e= | | 4x+4+30=90 |